KARAKTERISTIK INFORMASI TERKAIT CARA PENGGUNAAN METERED-DOSE INHALER DENGAN SPACER YANG MENGANDUNG KOMBINASI BETA-2 AGONIS DAN KORTIKOSTEROID OLEH APOTEKER DI APOTEK WILAYAH SURABAYA TIMUR - Amalia Lorensia; Doddy de Queljoe; Yessica Valensia (Jurnal Ilmiah Manuntung, 2018)
ABSTRACT Treatment of respiratory disorders using a metered-dose inhaler (MDI) with spacer becomes one of the important points. Pharmacists at pharmacies are the final key in therapy to ascertain how the use of inhalation tools is correct. This study aims to determine the completeness of each step of information on how to use MDI with spacer given by pharmacists at pharmacies in East Surabaya. The research design used is cross-sectional study with the subject of research is pharmacist in pharmacy. The research variable is the explanation of how to use MDI inhaler with spacer. An assessment method of 8 steps on how to use MDI with spacer and each number gets a value. Research subjects were 22 pharmacists. Most pharmacists describe each step orally by using the tool directly, ie at step: 1a (77.27%), 1b (77.27%), 2 (81.81%), 3 (31.81%) , 4a (59.09%), 4b (13.63%), 5a (100%), 5b (63.63%), 6a (90.90%), 6b (40.90%), 8a (9 , 09%), and 8b (9.09%). Most of the pharmacists explain verbally with a demonstration tool but only one pharmacist can explain all the steps completely. Therefore, pharmacists need to improve IEC services related to the use of MDI with a spacer for respiratory treatment. Keywords : information on how to use inhaler, Metered-Dose Inhaler (MDI), spacer, pharmacist, pharmacy